2005
DOI: 10.1002/elps.200500363
|View full text |Cite
|
Sign up to set email alerts
|

Glycine-based polymeric surfactants with varied polar head group: II. Chemical selectivity in micellar electrokinetic chromatography using linear solvation energy relationships

Abstract: A series of four acyl and four alkenoxy glycinates (i.e., mono-, di-, tri-, and tetraderivatives of polysodium N-undecenoyl glycinate (poly-SUGs) as well as polysodium N-undecenoxy carbonyl glycinates (poly-SUCGs)) were compared for simultaneous separation of nonhydrogen bonding (NHB), hydrogen-bond acceptor (HBA), and hydrogen-bond donor (HBD) solutes. An increase in the number of glycine units in the polar head group of polymeric surfactant decreases both the retention and the migration window of all solutes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…1B) and undecenoyl glycinate (SUG n , Fig. 1C) surfactants and polymers with one, two, three, or four glycine units as the head group were reported [28,29]. The CMC of the surfactants were observed to decrease by approximately a factor of two with the addition of each glycine unit, while the aggregation numbers increased.…”
Section: Achiral Polymersmentioning
confidence: 95%
See 1 more Smart Citation
“…1B) and undecenoyl glycinate (SUG n , Fig. 1C) surfactants and polymers with one, two, three, or four glycine units as the head group were reported [28,29]. The CMC of the surfactants were observed to decrease by approximately a factor of two with the addition of each glycine unit, while the aggregation numbers increased.…”
Section: Achiral Polymersmentioning
confidence: 95%
“…The polymers did, in some cases, show significant differences in selectivity toward geometrical isomers of phenylimidazole, nitrotoluene, or methoxyphenethylamine. LSER studies of the series showed few significant differences or trends among the PSPs, although the materials do appear to become more compact and cohesive as the number of glycinate units increases [28].…”
Section: Achiral Polymersmentioning
confidence: 98%
“…Some significant selectivity differences were observed for certain geometrical isomers as well as for nonhydrogen bonding solutes. LSER studies indicated that the materials appear to become more resistant to the formation of a solvation cavity as the number of glycinate units is increased [55].…”
Section: Structural Studiesmentioning
confidence: 99%
“…2A) and undecenoyl glycinate (Fig. 2B) surfactant monomers and polymers with one to four glycine units at the head group were studied with regard to solvation character and performance [55,56]. The CMCs of the monomers decreased by a factor of approximately 2 with the addition of each glycine unit, while the aggregation numbers increased.…”
Section: Structural Studiesmentioning
confidence: 99%
“…26,27 Structurally, polymeric surfactants are very similar to conventional micelles, but form spherical aggregates, which are covalently linked via the hydrophobic tails, while the polar head groups remain on the outside of the aggregate. 28,29 Several studies have shown the influence on chemical selectivity in MEKC [30][31][32] is dependent on the polar head group and the hydrocarbon chain length. Therefore, it would be favorable to incorporate such polymeric surfactant monomers in the MIP-NP process.…”
mentioning
confidence: 99%